The Social Power Ideology between Buddhist and Islam Represented in Times Magazine - Mirfa’un Nu’ma (Fakultas Agama Islam, Universitas Hasyim Asy'ari, 2022)
This study aimed to determine the critical discourse analysis of news about Rohingya refugees published by theTimes magazine.The qualitative descriptive method is used as the basis for thinking, and thecritical paradigm is used as the point of view of this analysis. The theoryused is the theory of Power and Domination from Teun Van Dijk. The subject of this research is a discourse leaked by the Times magazine entitled